2007
DOI: 10.1128/cvi.00344-06
|View full text |Cite
|
Sign up to set email alerts
|

Social Mixing with Other Children during Infancy Enhances Antibody Response to a Pneumococcal Conjugate Vaccine in Early Childhood

Abstract: Children who have siblings and/or who attend day care have higher rates of nasopharyngeal colonization with pneumococci than lone children do. Pneumococcal colonization is usually asymptomatic but is a prerequisite for invasive disease. We studied the effect of social mixing with other children on immunity to a pneumococcal vaccine. One hundred sixty children aged 1 year were immunized with a 7-valent conjugate pneumococcal vaccine. A blood sample was obtained before and 9 to 11 days after the vaccine. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
1
12
1
Order By: Relevance
“…In 1 study, the administration of 1 dose of PCV7 to 1-year-old toddlers resulted in significantly lower anti-9V antibody concentration 9-11 days after immunization in 8 children carrying S. pneumoniae serotype 9V at the time of immunization than in 152 children not carrying this serotype [39]. However, no significant differences were demonstrated for the other serotypes.…”
Section: Discussioncontrasting
confidence: 45%
“…In 1 study, the administration of 1 dose of PCV7 to 1-year-old toddlers resulted in significantly lower anti-9V antibody concentration 9-11 days after immunization in 8 children carrying S. pneumoniae serotype 9V at the time of immunization than in 152 children not carrying this serotype [39]. However, no significant differences were demonstrated for the other serotypes.…”
Section: Discussioncontrasting
confidence: 45%
“…Serotype 4 induced the best IgA response following the primary immunization. This may be one reason for the low rates of detection of this serotype in carriage studies, and a lack of carriage in adults and toddlers may explain the similarity in response to this serotype following primary immunization (11,24,61,65).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the response to the primary dose of conjugate in this age group looks more like a naïve response than that seen in adults, even though the vaccine is conjugated. The absence of naturally acquired, polysaccharide-specific IgG B-cell memory in the toddlers prior to immunization might be related to a lack of priming via the nasopharyngeal carriage of pneumococci, except that a number of epidemiological studies have clearly shown that 80% of toddlers have carried the vaccine or vaccine-related serotypes of pneumococci by 1 year of age (10,36,40,61,65). These observations suggest that the amount of pneumococcal carriage experienced during the first year of life may not be sufficient to maintain the levels of IgG or the elevated frequencies of IgG memory B cells against all serotypes in this age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…69,70 Exposure to a greater number of serotypes also enhances immune responses. 71 In addition to anti-capsular antibodies, colonization in humans and in …”
Section: Immunizing Effect Of Colonizationmentioning
confidence: 99%